2002
DOI: 10.1121/1.1428262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prosodic factors on spectral dynamics. I. Analysis

Abstract: The effects of prosodic factors on the spectral rate of change of vowel transitions are investigated. Thirty two-syllable English words are placed in carrier phrases and read by a single speaker. Liquid-vowel, diphthong, and vowel-liquid transitions are extracted from different prosodic contexts, corresponding to different levels of stress, pitch accent, word position, and speaking style, following a balanced experimental design. The spectral rate of change in these transitions is measured by fitting linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 30 publications
(34 reference statements)
0
19
1
1
Order By: Relevance
“…Contrary to previous clear speech studies (Ferguson & Kewley-Port, 2007;Ferguson & Quené, 2014;Lam et al, 2012;Moon & Lindblom, 1994;Wouters & Macon, 2002; but see Tasko & Grelick, 2010), F2 slope was not affected by any of the nonhabitual conditions. Methodological factors may explain why findings from the current study are different from those reported in previous clear speech studies.…”
Section: Condition Effects: Segmental Measurescontrasting
confidence: 54%
See 2 more Smart Citations
“…Contrary to previous clear speech studies (Ferguson & Kewley-Port, 2007;Ferguson & Quené, 2014;Lam et al, 2012;Moon & Lindblom, 1994;Wouters & Macon, 2002; but see Tasko & Grelick, 2010), F2 slope was not affected by any of the nonhabitual conditions. Methodological factors may explain why findings from the current study are different from those reported in previous clear speech studies.…”
Section: Condition Effects: Segmental Measurescontrasting
confidence: 54%
“…For example, clear speech studies have reported increased VSAs (Bradlow, Kraus, & Hayes, 2003;Ferguson & Kewley-Port, 2002Johnson, Flemming, & Wright, 1993;Lam et al, 2012;Moon & Lindblom, 1994;Picheny, Durlach, & Braida, 1986; but see Krause & Braida, 2004) and increased rates of spectral change in clearly produced monophthongs, diphthongs, and liquid transitions relative to conversational speech (Ferguson & Kewley-Port, 2007;Ferguson & Quené, 2014;Lam et al, 2012;Moon & Lindblom, 1994;Wouters & Macon, 2002; but see Tasko & Greilick, 2010). Clear speech effects have also been studied in consonants produced by healthy speakers, wherein clearly produced fricatives tend to be longer in duration (Maniwa, Jongman, & Wade, 2009).…”
Section: Clear Speech Acoustic Adjustmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it should be noted that changes in the rate of formantfrequency change are common concomitants of changes in speech rate (e.g., Pitermann 2000; Wouters and Macon 2002;Weismer and Berry 2003). For example, the data reported by Weismer and Berry (2003) show that, for each of their six talkers, increases in speech rate of CVC syllables resulted in increases in the rate of second formant transitionsmean F2 rate of change (estimated from their Figure 5) increased from 4.9 Hz/ms for the slowest speech rate to 12.4 Hz/ms for the fastest, a fast/slow ratio of 2.5.…”
Section: Figmentioning
confidence: 99%
“…Vowel duration (Edwards, Beckman & Fletcher 1992), formant transitions in diphthongs (Wouters & Macon 2002), glottalistion (Dilley, Shattuck-Hufnagel & Ostendorf 1996), and consonant realisation (Fougeron & Keating 1997) all appear to be linked to prosodic position; greater articulatory effort tends to be observed at the edges of prosodic domains (Fougeron & Keating 1997). While only one of the analysed tokens in the current study occurred at a sentence boundary, this does not ensure that the observed phonetic differences between the different functions of like were not in fact due to the token's prosodic position in the sentence.…”
Section: Prosody and Phonetic Variationmentioning
confidence: 99%